Subnexuses Based on N-structures
The notion of a subnexus based on N -function (briefly, N -subnexus) is introduced, and related properties are investigated. Also, the notions of N -subnexus of type (α, β), where (α, β) is (, ), (, q), (, \! q), (q, ), (q,q), (q, \! q), (, ) and (, q), are introduced, and their basic properties are investigated. Conditions for an N -structure to be an N -subnexus of type (q, \! q) are given, and characterizations of N -subnexus of type (, \! q) and (, q) are provided. Homomorphic image and preimage of N -subnexus are discussed. , number=10, journal=Armenian Journal of Mathematics, author=Norouzi, Morteza and Asadi, Ameneh and Jun, Young Bae, year=2022, month=Sep., pages=1–15